2019
DOI: 10.1093/jjco/hyz078
|View full text |Cite
|
Sign up to set email alerts
|

Predictive ability of prognostic nutritional index in surgically resected gastrointestinal stromal tumors: a propensity score matching analysis

Abstract: Prognostic nutritional index was found to be correlated with prognosis in GISTs before and after propensity score matching and its incorporation improved the prognostic stratification of NIH risk criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…However, LMR seemed to be irrelevant to the RFS of GIST patients, which is different from previous studies 14 . In addition, the PNI, a nutritional score based on albumin levels and lymphocytes, was also related to RFS of GIST patients before PSM and after PSM in present study 11,12 (Figure S1 ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, LMR seemed to be irrelevant to the RFS of GIST patients, which is different from previous studies 14 . In addition, the PNI, a nutritional score based on albumin levels and lymphocytes, was also related to RFS of GIST patients before PSM and after PSM in present study 11,12 (Figure S1 ).…”
Section: Discussionsupporting
confidence: 53%
“…Currently, some GIST-specific parameters based on postoperative pathologies, such as tumor size, primary tumor location, mitotic index, and tumor rupture, have been used to stratify the risk of recurrence for GISTs 2,[5][6][7] . Meanwhile, the recent effort has shed light on the role of preoperative cancer-related inflammation and nutrition status in cancer progression, such as gastric cancer 8 , colorectal cancer 9 , non-small lung cancer 10 , and gastrointestinal stromal tumor [11][12][13][14][15][16] . Several preoperative immuno-inflammatory-based prognostic scores, such as the preoperative neutrophil to lymphocyte ratio (NLR), the lymphocyte to monocyte ratio (LMR), and the platelet to lymphocyte ratio (PLR), reflect the systematic inflammatory response, with some evidence revealing that they are prognostic for GISTs [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The medians and ranges of the PLR, NLR, and PNI were 107.107 (19.770–566.842), 2.143 (0.076–37.496), and 47.646 (26.155–65.155), respectively. We chose the medians of the PLR, NLR, and PNI as the cutoff points to divide the patients into low and high groups, according to a previous study ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PNI, composed of albumin and lymphocytes, was initially used to evaluate the immunological and nutritional aspects of patients undergoing gastrointestinal tract surgery ( 29 ). Numerous previous studies have shown that low PNI was associated with poorer progression-free survival and overall survival in patients with malignant tumors, including high recurrence risk for GISTs ( 17 , 30 , 32 , 33 ). In this study, the results indicated that GIST patients with a low PNI had shorter RFS than those with a high PNI.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation